Webcluq: da divulgação científica à motivação para aprendizagem de química a partir de podcasts - Vasconcelos Júnior, João Batista de (2020)
One of the challenges of teaching chemistry is to review the way this science is worked in high school. With the idea of demystifying the teaching of Chemistry, this work followed the proposal of using experimental projects and approaching important themes combined with digital technologies, through podcasts that increase didactics, becoming an alternative tool for teaching Chemistry. This search for viable and effective solutions, combined with the use of technology and the Web, can, with normal cost, result in a more dynamic teaching with regard to this science. Thus, this study aims to analyze the motivation for learning Chemistry, in the 2nd grade of high school, from scientific dissemination, through virtual platforms of experiences with experimental activities and discussions of topics related to Chemistry, in a Chemistry club, the WebCluq. The evaluation was carried out through two questionnaires applied before and after students' contact with the podcasts that underwent a pre-production, production and distribution by the members of the Chemistry Club for the students of the 2nd grade classes of the school where it was held research, this took place both in a virtual environment, as well as reproduced on school radio. The podcasts portrayed the history of Chemistry or simply told a story related to some content. The dissemination of all material produced occurred on the Web, in messaging applications, social networks and school radio. From these experimental and theoretical actions with relevant themes, the student's approach to Chemistry was verified, in addition to the projection for scientific dissemination of Chemistry, situations aimed at advancing a maturity that motivated the development of competences and skills necessary for a closer relationship. with this critical science of nature.